Immunization status in childhood cancer survivors: A hidden risk which could be prevented - Najwa Yahya Fayea; Ashraf Elsayed Fouda; Shaimaa Mohamed Kandil (Elsevier, 2017)
Background: A limited number of studies have examined the vaccine-specific antibody status of children with cancer. There are disagreements over the guidelines for postcancer immunization strategy. Methods: Our study was an observational, cross-sectional retrospective review of data collected on children who were seen in the outpatient clinic at King Abdullah Medical City, Oncology Center, Jeddah, the Kingdom of Saudi Arabia. Our aim was to evaluate the seropositive status to vaccine-preventable diseases: measles, mumps, rubella, diphtheria, tetanus, polio, and Haemophilus influenzae type B (HIB) in childhood cancer survivors at our center in order to plan future vaccination for these children and establish a simple revaccination schedule. Results: Forty-seven patients (21 boys and 26 girls) were included in the study. Age at the time of cancer diagnosis (mean±standard deviation) was 5.68±3.79 years and age at test sampling was 10.68±3.79 years. Acute leukemia was the most common cancer (49% of patients), followed by lymphoma (28%), brain tumors (13%), and solid tumors (10%). Treatment intensities (according to the Treatment Intensity Rating Scale, version 3.0; ITR-3) were 2, 3, and 4 for 26 patients (55%), 20 patients (43%), and one patient (2.1%), respectively. We found that 93% of our patients were considered seronegative (unprotected) for at least one vaccine-preventable disease. The seronegative rates for measles, mumps, rubella, diphtheria, tetanus, polio, and HIB were 46.8%, 36.2%, 36.2%, 46.8%, 61.7%, 17.1%, and 42.6%, respectively. Criteria including age at diagnosis, age at sampling, type of malignancy, and treatment intensity were not significantly different between seropositive and seronegative patients. Conclusion: Seronegative rates for vaccine-preventable diseases were very high in childhood cancer survivors, which represented a subpopulation of high-risk patients who could benefit from revaccination. We suggest a universal revaccination approach for all childhood cancer survivors, which is easily applicable and of low cost. Key Words: childhood cancer survivors, immunization, vaccine